2019
DOI: 10.26444/aaem/105391
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic lipid profile and health behaviours in women post-menopause working in agriculture

Abstract: Introduction and objective. There is a significantly higher risk of lipid disorders occurrence, including atherogenic dyslipidemia in women after menopause than it is in general population. The aim of the work was to investigate the correlation between health behaviours and the occurrence of lipid disorders in women after menopause working in agriculture. Material and methods. The study was conducted in years 2015-2016 and included 843 post-menopausal women working in agriculture. The following were used: a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Al, who showed that serum TC, TG and LDL were elevated and serum HDL decreasesd in post-menopausal women. [21][22][23] Hypercholesterolemia in postmenopausal women is due to impairment of the LDL receptor. 24 Serum TC is an independent risk factor for CVD and every 1% rise in TC is associated with at least 2% increase in the incidence of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Al, who showed that serum TC, TG and LDL were elevated and serum HDL decreasesd in post-menopausal women. [21][22][23] Hypercholesterolemia in postmenopausal women is due to impairment of the LDL receptor. 24 Serum TC is an independent risk factor for CVD and every 1% rise in TC is associated with at least 2% increase in the incidence of CVD.…”
Section: Discussionmentioning
confidence: 99%